Cover Feature: Facile Synthesis and Characterization of Pure Tochilinite‐like Materials from Nanoparticulate FeS (Z. Anorg. Allg. Chem. 23/2022) - Bolney, Robert; Grosch, Mario; Winkler, Mario; Slageren, Joris; Weigand, Wolfgang; Robl, Christian (Zeitschrift für anorganische und allgemeine Chemie (1950), 2022)
The cover picture shows that pure tochilinite‐like samples can be prepared from nanoparticulate FeS with mackinawite structure under mild hydrothermal conditions. The samples have been characterized by various methods including Mössbauer spectroscopy. TEM and SEM revealed the tochilinite analogues to consist mainly of thin sheets accompanied by nanotubes. The following compositions could be determined: Fe0.76S*0.86[Fe2+0.01Fe3+0.56Mg2+0.43(OH)2.01], Fe0.89S*0.85[Fe2+0.55Fe3+0.11Al3+0.33(OH)1.84(O)0.16], and Fe0.71S*0.79[Fe2+0.25Fe3+0.73Mg2+0.01Al3+0.01(OH)1.98(O)0.02]. More details are discussed in the article by R. Bolney, M. Grosch, M. Winkler, J. van Slageren, W. Weigand, and C. Robl (DOI: 10.1002/zaac.202200219).